Role of Indian Railways in Economic Growth of India - Ali, Sanauar; Singh, Ram Chandar (Journal of Commerce and Trade, 2017)
Indian Railway is the only way by which can an average India Travel from Kashmir to Kanya kumari and from Gujarat to Assam. It Is an entity which has over 150 years of history with a network length of about 66030 km. (Third largest world) it carries 23 Million passenger per day with the Annual freight carrying capacity of 3 Billion tones it is an entity which employs Around lakh people (Seventh largest employer in the world) Despite such staggering figures, India Railway is suffering the vicious cycle of underinvestment. This has led to severe congestion in high density network and over utilization of existing network between meters underinvestment in Railway has led to poor progress in capacity augmentation, compromise a safety a decline is standers of service Reduced efficiency and such optimal freight and passengers traffic. With Reduced budgetary support over the post few, years, Railway has to raise resources from it Revenue to invest in its own infrastructure with Recued revenues from freight due to higher changes than road network and crass sublimation of passenger fair with freight revenue India Railways is left with meager resources to even Replace- its depreciating Assets than augmenting capacity. This has led to negative multiplier effect which has further Reduced Resources for Railways. Despite such challenges post Railway budgets (2018 Budget of Railway was an exception) have focused on populist measure Rather creating the infrastructure to support India Growing economics Ambitions.